2018
DOI: 10.3892/etm.2018.6731
|View full text |Cite
|
Sign up to set email alerts
|

High FNDC1 expression correlates with poor prognosis in gastric cancer

Abstract: Gastric cancer is a common human cancer worldwide. Fibronectin is an important extracellular matrix protein that has been implicated in many cancers and is known to be associated with proliferation and migration. Fibronectin type III domain containing 1 (FNDC1) contains a major component of the structural domain of fibronectin. The objectives of the present study were to measure FNDC1 expression in gastric cancer tissues and evaluate its value as a potential prognostic marker for gastric cancer. FNDC1 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(57 reference statements)
1
7
1
Order By: Relevance
“…Furthermore, the expression of FNDC1 was not associated with DFS in patients with BC. By contrast, previous studies have suggested that the expression of FNDC1 was associated with prognosis in gastric cancer (11,14). These results suggested that the role of FNDC1 in tumors is complicated.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, the expression of FNDC1 was not associated with DFS in patients with BC. By contrast, previous studies have suggested that the expression of FNDC1 was associated with prognosis in gastric cancer (11,14). These results suggested that the role of FNDC1 in tumors is complicated.…”
Section: Discussioncontrasting
confidence: 61%
“…Some scholars have found that the upregulation of microRNA-1207-3p can significantly inhibit the migration and proliferation of tumors in the study of prostate cancer, further verifying that it can induce tumor cell apoptosis by regulating the downstream target gene FNDC1 (7). Recent studies have also reported a correlation between the expression of FNDC1 in GC and clinical characteristics of patients, reporting that the overexpression of FNDC1 is associated with poor prognosis of patients (8)(9)(10). In our previous study (4), molecular markers of PM were analyzed by WES and FNDC1 was found to have a higher frequency of mutations in PM patients, suggesting that FNDC1 may be associated with GC invasion and PM.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have found that FNDC1 is closely related to the development of many diseases including various tumors (5)(6)(7). Recent studies have reported a correlation between the expression of FNDC1 in GC and clinical characteristics of patients (8)(9)(10). However, the exact role of FNDC1 in GC and the potential molecular mechanism has not been fully elucidated, and the effect of FNDC1 on PM remains to be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…FNDC1 was also shown to promote apoptosis through hypermethylation in human salivary-like cystic carcinoma cells [ 36 ]. Additionally, high FNDC1 expression was also reported to be associated with poor prognosis in gastric cancer [ 37 ], which is consistent with our findings. INHBA encodes a member of the TGF-beta superfamily of proteins, which has been found to be associated with various types of human cancers.…”
Section: Discussionsupporting
confidence: 92%